Chamomile Production Site in World - Zahirian, Gul Ahmad (Journal of Natural Sciences – Kabul University, 2023)
Chamomile plant has a branched, erect and smooth stem, which grows to a height of 15–60 cm. The flowers contain a blue essential oil, what gives it the characteristic smell and interesting properties. This colour characteristic of the oil, attributable to the chamazulene it contains, explains why the plant is also known by the common name Blue Chamomile. More than 120 chemical constituents have been identified in chamomile flower. The most of them are found in the blue essential oil of the flowers. Chamomile is used in herbal medicine. For the cultivation of chamomile, the soil needs no special quality although the crop grows best on well balanced soils with good topsoil. The chamomile plant often flowers 2 to 3 times per year. This is taken into account by multiple harvests per year as well. The flowering period is about 50–65 days while the development of a flower takes about 20–25 days.